Faktor Eksternal dan Faktor Internal yang Mempengaruhi Perilaku Auditor dalam Penghentian Prematur Prosedur Audit - Reni Yendrawati; Wenny Hartanti Putri (Jurnal Aplikasi Bisnis, 2016)
This study aims to analyze whether Time Pressure, Risk Audit, Materiality, Procedures Review and Control of Quality, Supervision Measures, External Locus of Control and Self Esteem auditor effect on premature sign off audit procedures. Data collection was conducted by giving questionnaires to auditors working in KAP Yogyakarta. The method of data analysis is validity and reliability testing, hypothesis testing by means of logistic regression analysis and Friedman test. Hypothesis testing is first performed using the Friedman test and the second to the eighth hypothesis using logistic regression. Friedman test showed that there is a priority order audit procedure that are likely to be abandoned. From the results mean rank from Friedman test indicates that the use of information management assertion is a procedure that is often to be abandoned, while the physical examination is the procedure most often to be abandoned. From the logistic regression showed that time pressure, review and quality control procedures, supervision measures, external locus of control and self-esteem have a significant effect on premature sign of audit procedures. But the audit risk and materiality has no affect the premature termination of audit procedures.